Presenteism and associated factors in a reference hospital in Covid-19: a cross-sectional study - Naiana Pacifico Alves; Andressa Carneiro Moreira; Neide Maria Silva Gondim Pereira; Rhanna Emanuela Fontenele Lima de Carvalho; Tânia Solange Bosi de Souza Magnago (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To identify the occurrence of presenteeism in healthcare professionals and its association with socio-occupational and health factors. Method: Cross-sectional study, carried out from July to October 2022 with 152 healthcare professionals from a reference hospital for COVID-19. A semi-structured questionnaire was applied for socio-occupational and health characterization, and the Stanford Presenteeism Scale. Prevalence ratios were used to evaluate associations and statistical significance using Pearson's X2; binary logistic regression to investigate the impact of socio-occupational variables on presenteeism and linear regression for the scale domains. Results: Female (65.8%), mean age 32±8.59 years, no children (68.4%), nursing staff (55.3%), no previous (74.4%) or acquired (87.5%) comorbidities. Of the total, 85 (55.93%) professionals had low presenteeism. Previous comorbidity χ2(1)=6.282;p=0.012, sick leave (χ2 (1)=7.787;p=0.005, R2 Negelkerke= 0.069) and medication use (χ2 (1)=8.565;p=0.003, R2 Negelkerke= 0.077) were predictors of low presenteeism. Conclusion: There was no significant association between sociodemographic variables and presenteeism. Previous comorbidity, absence from work for health reasons and the use of medication were significant predictors of reduced concentration in work activities.